Problems relating to valuation of variation rules in government's lump sum contract - Ling, Yean Yng. (2009)
Construction contracts, unlike most other commercial contracts, make provisions for the architect to issue changes to the original contract. These changes could be in the form of additional works, omission or modification of works to the contract. Many problems arise from these, such as valuation for the changes in order to compensate the contractor, disruption to the contractor's work flow and argument on whether the contract period will be affected. Problems relating to variations will sometimes lead to dispute among the architect, employer and contractor.